2004
DOI: 10.1590/s0041-87812004000300001
|View full text |Cite
|
Sign up to set email alerts
|

Dental and facial characteristics of patients with juvenile idiopathic arthritis

Abstract: OBJECTIVE: It has been shown that the temporomandibular joint is frequently affected by juvenile idiopathic arthritis, and this degenerative disease, which may occur during facial growth, results in severe mandibular dysfunction. However, there are no studies that correlate oral health (tooth decay and gingival diseases) and temporomandibular joint dysfunction in patients with juvenile idiopathic arthritis. The aim of this study is to evaluate the oral and facial characteristics of the patients with juvenile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
18

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 8 publications
2
38
0
18
Order By: Relevance
“…8 In this regard, chronic arthritis with upper limb disability and reduced mandibular mobility due to temporomadibular joint involvement was reported to be an important contributing factor for PD in our JIA patients. 32 Furthermore, a signifi cant increased level of poor oral hygiene in patients with JIA was found. 35 On the other hand, one study showed that if cofactors (such as: age, gender and smoking) are included, the microbial plaque (and not the JIA diagnosis) is related to periodontitis.…”
Section: Juvenile Idiopathic Arthritis (Jia)mentioning
confidence: 98%
See 2 more Smart Citations
“…8 In this regard, chronic arthritis with upper limb disability and reduced mandibular mobility due to temporomadibular joint involvement was reported to be an important contributing factor for PD in our JIA patients. 32 Furthermore, a signifi cant increased level of poor oral hygiene in patients with JIA was found. 35 On the other hand, one study showed that if cofactors (such as: age, gender and smoking) are included, the microbial plaque (and not the JIA diagnosis) is related to periodontitis.…”
Section: Juvenile Idiopathic Arthritis (Jia)mentioning
confidence: 98%
“…[28][29][30] Several studies, [29][30][31][32][33][34] reporting that JIA could be a risk factor for gingivitis or periodontitis and these pediatric conditions were included in the current system classifi cation of PD. 8 In this regard, chronic arthritis with upper limb disability and reduced mandibular mobility due to temporomadibular joint involvement was reported to be an important contributing factor for PD in our JIA patients.…”
Section: Juvenile Idiopathic Arthritis (Jia)mentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile rheumatoid arthritis is a disease with oral involvement with anterior open bite, limited mouth opening, and in most of the cases, compromises the temporomandibular joint (Savioli et al 2004;Carvalho et al 2012) …”
Section: Craniofacial Anomaliesmentioning
confidence: 99%
“…Sendo assim, novos aspectos devem ser considerados no acompanhamento destes pacientes, tais como o comprometimento da massa óssea e alterações da saúde oral, que podem estar associadas ao processo inflamatório decorrente da atividade da doença e/ou do uso crônico de glicocorticoides (GC) e imunossupressores [8][9][10][11] .…”
Section: Lista De Figurasunclassified